Antimicrobial Activity of Soaked and Boiled Jengkol Fruit Skin Extract against Staphylococcus aureus, Escherichia coli and Candida albicans - Nurmiati, Nurmiati; Periadnadi, Periadnadi; Apriyelita, Annisa (Jurnal Biologi Tropis, 2024)
Jengkol (Archidendron jiringa) fruit skin contains saponin, tannin, flavonoid, and phenolic compounds which act as antimicrobials in inhibiting and killing microbial. This research aimed to analyze the differences in various jengkol fruit skin extracts in antimicrobial activity against test microbes, as well as to analyze the total phenolic content and total saponin content in each jengkol fruit skin extract. The research method was carried out using an experimental method. Factor A extract (soaking and boiling) and Factor B Microbe (Staphylococcus aureus, Escherichia coli, Candida albicans). The results of this research showed that extracts from soaking and boiling of jengkol fruit skin provided different inhibitory effects on the growth of S. aureus, E. coli, C. albicans. The best extraction method that produces the largest zone of inhibition for test microbes is boiling extract. The extract with the highest total phenolic content is boiling extract with a total phenolic content of 7.517 mgGAE/ml. The extract with the highest total saponin content is boiling extract with a total saponin content of 16.11%.